Strategi Komunikasi PT. Samsung dalam Mempertahankan Reputasi Perusahaan Melalui Program Solve for Tomorrow - Ennita LPS; Edison Bonar Tua Hutapea (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the communication strategies used by PT. Samsung in maintaining the company's reputation through the Solve for Tomorrow, a CSR program. Using a descriptive qualitative method, this research analyzes data obtained from various sources, including the company's website, press releases, and interviews. The results showed that PT. Samsung has implemented effective communication strategies, such as public relations and using appropriate communication channels such as media relations, and utilization of social media. The communication strategies used have succeeded in building a positive image of the company in the eyes of the public, especially the younger generation. This research concludes that an effectively communicated CSR program can be a solution to improve the company's reputation.